2022
DOI: 10.1213/ane.0000000000005878
|View full text |Cite
|
Sign up to set email alerts
|

Association of Medicaid Expansion With Neuraxial Labor Analgesia Use in the United States: A Retrospective Cross-Sectional Analysis

Abstract: BACKGROUND: The Affordable Care Act has been associated with increased Medicaid coverage for childbirth among low-income US women. We hypothesized that Medicaid expansion was associated with increased use of labor neuraxial analgesia. METHODS: We performed a cross-sectional analysis of US women with singleton live births who underwent vaginal delivery or intrapartum cesarean delivery between 2009 and 2017. Data were sourced from births in 26 US states that used the 2003 Revised US Birth Certificate. Differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
2
5
0
Order By: Relevance
“…reported that the Medicaid expansion was associated with a 1.5% (95% CI, 0.2 to 2.9) increase in the labor neuraxial analgesia utilization rate among nulliparous women in states that expanded Medicaid compared to nulliparous women in states that did not expand Medicaid. 28 This effect size is similar to the one observed in our study, and although statistically significant, is also unlikely of clinical significance.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…reported that the Medicaid expansion was associated with a 1.5% (95% CI, 0.2 to 2.9) increase in the labor neuraxial analgesia utilization rate among nulliparous women in states that expanded Medicaid compared to nulliparous women in states that did not expand Medicaid. 28 This effect size is similar to the one observed in our study, and although statistically significant, is also unlikely of clinical significance.…”
Section: Discussionsupporting
confidence: 90%
“…For example, a regression coefficient of 0.012 indicates that the Dependent Coverage provision is associated with a 1.2% (absolute) increase in the probability of labor neuraxial analgesia in women aged 21 to 25 yr compared to women aged 27 to 31 yr. †Adjustment used the following variables: (1) race and ethnicity, (2) education level, (3) marital status, (4) county of residence core base statistical area classification, (5) county of residence percent persons in poverty, (6) county of residence percent unemployed, (7) prepregnancy body mass index, (8) preexisting diabetes, (9) gestational diabetes, (10) preexisting hypertension, (11) gestational hypertension, (12) previous cesarean section, (13) Analyzing birth certificate data, Xiao et al reported that the Medicaid expansion was associated with a 1.5% (95% CI, 0.2 to 2.9) increase in the labor neuraxial analgesia utilization rate among nulliparous women in states that expanded Medicaid compared to nulliparous women in states that did not expand Medicaid. 28 This effect size is similar to the one observed in our study, and although statistically significant, is also unlikely of clinical significance.…”
Section: Perioperative Medicinesupporting
confidence: 90%
See 1 more Smart Citation
“…13 Several of the articles in this issue have used large databases appropriately to report on diverse topics spanning from coronavirus disease 2019 (COVID-19), the impact of Medicaid expansion on the use of neuraxial labor analgesia, and the association between changes in postoperative opioid utilization and longterm health care spending among surgical patients with chronic opioid utilization. [14][15][16] The paper by Sun 16 examining opioid utilization highlights the important evolving area of value-based care and the triple aim. Porter 17 defined value in health care as the quality of outcomes achieved over spent costs.…”
mentioning
confidence: 99%
“…13 Several of the articles in this issue have used large databases appropriately to report on diverse topics spanning from coronavirus disease 2019 (COVID-19), the impact of Medicaid expansion on the use of neuraxial labor analgesia, and the association between changes in postoperative opioid utilization and long-term health care spending among surgical patients with chronic opioid utilization. 14–16…”
mentioning
confidence: 99%